(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The noninvasive detection and reconstruction of 3D temperature field in a biological body have received increasing attention in bio-medical engineering field. Based on the classical Pennes bioheat transfer equation, the heat transfer mathematical model fitting for breast tissue is founded in this paper. Meanwhile, using the large analysis software ANSYS, the modeling and simulating of heat transfer in pork and intravital breast tissue are presented combining with Finite Element Method (FEM). The result shows, the 3D temperature field can be well reconstructed efficiently, which will play a positive role in promoting many research field such as tumor thermotherapy, cryosurgery, cryo-preservation of biomaterial and so on.